Innovative technologies in learning foreign languages - Jo’rayeva Shohida Choriyevna; Asliddin Usmonov (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
this article deals with the necessity and importance of innovative technology in the foreign language classroom. It also discusses in detail multimedia technology acting as a method for special intellectual activity.This technology has a number of advantages compared with other information technology training. The use of innovative learning technology creates the most favorable conditions and contributes significantly to motivation in learning foreign languages.